Analysis of Financial Performance Between Banking and Non-Bank Financial Institutions: Evidence from PT Bank Central Asia Tbk and PT Mandala Multifinance Tbk - Annisa Paramaswary Aslam (Abadi Institute, 2026)
This study aims to analyze and compare the financial performance of banking institutions and non-bank financial institutions in Indonesia through a case study of PT Bank Central Asia Tbk (BCA) and PT Mandala Multifinance Tbk. The research employs a descriptive comparative approach using financial statement data from 2022 to 2024. The analysis focuses on financial position statements, income statements, and key financial ratios that reflect profitability, operational efficiency, asset quality, and capital structure. The results show that BCA has significantly larger assets and more stable profitability compared to Mandala Multifinance due to its banking intermediation function and access to public deposits. Meanwhile, Mandala Multifinance demonstrates relatively higher asset turnover and return on assets due to its focus on consumer financing activities. In terms of operational efficiency, BCA shows stronger performance with a lower operating expense ratio, whereas Mandala Multifinance has higher operational costs due to the nature of consumer financing operations. The findings indicate that although both institutions operate in the financial industry, differences in business models and funding sources result in distinct financial performance characteristics.